2020
DOI: 10.1080/02670844.2020.1711631
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of titanium and the Ti-6Al-7Nb alloy after isothermal oxidation

Abstract: The purpose of the study was to determine optimal oxidation parameters of titanium Grade 2 and Ti-6Al-7Nb alloy in order to obtain the best structural, mechanical and tribological characteristics of oxide layers. It has been shown that the morphology of oxide layers depends on the oxidation temperature and the continuity of layers increased as the oxidation temperature rose. The examinations of the phase composition after oxidation showed mainly the presence of TiO 2 in the crystallographic form of rutile. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…The production of oxide layers by isothermal oxidation enables a significant improvement in the mechanical properties (hardness) of the Ti-6Al-7Nb alloy. As it results from the previous studies presented in [32], the surface hardness of the Ti-6Al-7Nb alloy can be increased even several times and is strictly dependent on the temperature and time parameters of the oxidation process. The most important parameter influencing the increase in hardness of the obtained oxide layers is the oxidation temperature.…”
Section: Introductionsupporting
confidence: 51%
“…The production of oxide layers by isothermal oxidation enables a significant improvement in the mechanical properties (hardness) of the Ti-6Al-7Nb alloy. As it results from the previous studies presented in [32], the surface hardness of the Ti-6Al-7Nb alloy can be increased even several times and is strictly dependent on the temperature and time parameters of the oxidation process. The most important parameter influencing the increase in hardness of the obtained oxide layers is the oxidation temperature.…”
Section: Introductionsupporting
confidence: 51%
“…They observed activation energies of oxidation between 600 and 700 °C were 276 and 191 kJ/mol -1 , respectively, for an oxidation duration of 72 h. Kumar et al 34 studied the oxidation kinetics of CP Ti alloy and observed 275 kJ/mol -1 activation energy at oxidation temperatures between 500–800 °C (up to 72 h exposure period). Also, Aniołek 35 observed 278 kJ/mol -1 activation energy of CP titanium alloy at oxidation temperatures between 600–800 °C for 72 h oxidation duration. However, 170 kJ/mol -1 activation energy for Ti–6Al–7Nb alloy was found at the same values.…”
Section: Resultsmentioning
confidence: 95%
“…The activation energy (Q ox ) for the oxidation of equiaxed TC21 alloy (for 50 h) was determined as 232 kJ mol −1 . The activation energies of Ti-6Al-4 V alloy at oxidation between 600 and 700 °C were 276 and 191 kJ mol −1 , respectively, for 72 h. The activation energies of commercially pure (CP) Ti alloy at oxidation temperatures between 500 and 800 °C were 275 kJ mol −1 for 72 h. The activation energy for Ti–6Al–7Nb was 170 kJ mol −1 19 , 47 , 48 .…”
Section: Resultsmentioning
confidence: 99%